PERSONALIZED SERVICES FOR COMMERCIAL ESTABLISHMENTS USING PLASERES - DIAZ, DAVID MARIN; ZULUAGA, ALEJANDRO RICO; CARRILLO-RAMOS, ANGELA; ARIAS BAEZ, MARIA PAULA; BARRAZA-URBINA, ANDREA (Journal of Mobile Multimedia, 2011)
This paper presents the application of adaptation aspects defined in IAM (acronym in English of Integrated Adaptation Model) on the platform “PlaSerEs”. The main goal of this platform is to provide personalized information about the products and/or services provided by commercial establishments to their clients. This platform is structured in four layers: i) the adaptation layer, composed of four modules: context, access device, user and wireless connection. ii) The general services layer, iii) the personalized services layer and, iv) the application layer. In order to validate and to evaluate how “PlaSerEs” works, we developed a functional prototype for a restaurant. This prototype works on Mobiles Devices (MD).